La imitación en el desarrollo del comportamiento de los niños de primer año de educación general básica de la Unidad Educativa Capitán Edmundo Chiriboga de la ciudad de Riobamba, periodo 2020 – 2021 - Trávez Angueta, Jakelin Paulina (2021)
Learning by imitation is a mechanism that allows the individual to acquire new knowledge through observation, so that children acquire through imitation behaviors, expressions and skills, thus strengthening their intellectual capacity. Therefore, such learning is an effective tool within education. The objective of this research is to determine how imitation affects the behavior of first-year children of basic general education of Captain Edmundo Chiriboga Educational Unit of the city of Riobamba province of Chimborazo. The development of the proposal has been carried out with a mixed research approach since it is research of a pedagogical social nature, and it includes teacher´s criterion. The methodology used is bibliographic type, since information related to the subject was obtained from various sources such as articles, books and journals. The instrument used is the survey aimed at the teacher and the TADI test applied to the 37 children who make up the “F” parallel. Through the interpretation of data, it was concluded that the family nucleus is the first influential model in the behavior of children, in addition, the imitation of the peers helps them to expand the social competencies, empathy, self-regulation skills and social perception